IMPLEMENTATION OF TECHNOLOGY, INFORMATION, AND COMMUNICATION LITERACY SKILLS IN THE MANAGEMENT OF LEARNING ADMINISTRATION TOOLS BY ELEMENTARY SCHOOL TEACHERS IN CUKUH BALAK SUBDISTRICT - Muslim, Ahmad; AM, Juhri (Institut Bakti Nusantara, 2025)
This research aims to analyze the implementation of Technology, Information and Communication (ICT) literacy skills in the administrative management of learning devices by teachers at the Elementary School in Cukuh Balak District. This research uses a qualitative approach with a case study method. Data was collected through observations, semi-structured interviews with teachers and school principals, as well as analysis of administrative documents related to the use of technology. The research results show that the majority of teachers have basic skills in using Microsoft Word to compile learning documents systematically, although there are still obstacles in setting the format. Microsoft PowerPoint is used to create more interactive teaching materials, but presentation design training is still needed. Microsoft Excel is used to record attendance and manage student grades, but understanding complex formulas is still an obstacle. Apart from that, the use of the internet and cloud-based applications such as Google Docs makes it easier to access information and collaborate between educators. The conclusion of this research indicates that ICT literacy in educational administration has had a positive impact on teacher work efficiency. However, there are still obstacles such as limited time, access to equipment, and lack of hands-on practice-based training. Therefore, this research implies the need to increase more applicable ICT training, support technology infrastructure in schools, and form teacher communities to share experiences and strategies in utilizing technology.